Mitral valve flattening and parameter mapping for patient-specific valve diagnosis - Lichtenberg, Nils; Romano, Gabriele; Brcic, Andreas; Karck, Matthias; De Simone, Raffaele; Engelhardt, Sandy (International journal of computer assisted radiology and surgery, 2020)
Intensive planning and analysis from echocardiography are a crucial step before reconstructive surgeries are applied to malfunctioning mitral valves. Volume visualizations of echocardiographic data are often used in clinical routine. However, they lack a clear visualization of the crucial factors for decision making.
Gesehen am 28.04.2020